Laser‐Like Emission from a Sandwiched MoTe2 Heterostructure on a Silicon Single‐Mode Resonator. Issue 20 (26th July 2019) - Fang, Hanlin; Liu, Jin; Lin, Qiaoling; Su, Rongbin; Wei, Yuming; Krauss, Thomas F.; Li, Juntao; Wang, Yue; Wang, Xuehua
Abstract: Molybdenum ditelluride (MoTe2 ) has recently shown promise as a gain material for silicon photonics. Reliable single‐mode operation and material stability remain two of the major issues that need to be addressed to advance this exciting technology, however. Here, laser‐like emission from a sandwiched MoTe2 heterostructure on a silicon single‐mode resonator is reported. The heterostructure consists of a layer of MoTe2 sandwiched between thin films of hexagonal boron nitride. It is known that tellurium compounds are sensitive to oxygen exposure, which leads to rapid degradation of the exposed layers in air. By encapsulating the MoTe2 gain material, much improved environmental stability is observed. Using a recently introduced single‐mode resonator design, better control over the mode spectrum of the cavity is exercised and single‐mode operation with a wide free spectral range is demonstrated. At room temperature, a Q ‐factor of 4500 and a threshold of 4.2 kW cm −2 at 1319 nm wavelength are achieved. These results lend further support to the paradigm of 2D material‐based integrated light sources on the silicon platform. Abstract : This work demonstrates room temperature laser‐like emission at 1319 nm, with single‐mode operation. The combination of hexagonal boron nitride encapsulated MoTe2 and an unmembraned photonic crystal nanobeam cavity gives rise to a robust light‐emitting device. This design offers a feasible approach to realize an integrated light source on silicon platform.